Comparative Outcomes and Indications of Phakic Implantable Collamer Lens (ICL) Exchange or Explantation in Keratoconus versus Non-Ectatic Eyes at a Tertiary Eye Hospital in Iraq (Ukrainian Journal of Ophthalmology, 2026)
Objective: This study aimed to compare the indications, timing, and clinical outcomes of phakic implantable collamer lens (ICL) exchange or explantation between eyes with keratoconus and eyes without keratoconus or other corneal ectasia (non-ectatic eyes), and to evaluate factors associated with the need for secondary ICL intervention, at a tertiary eye hospital in Iraq. Methods: This retrospective record review included ICL (V4b) procedures performed between January 2022 and January 2024. Among 200 implanted eyes, 25 eyes (12.5%) underwent secondary surgery and were included for group comparison: keratoconus group (n=10) and non-ectatic group (n=15). Clinical data included visual acuity, refraction, intraocular pressure, endothelial cell density, corneal parameters, and vault. Comparative analyses were performed between groups, with p
Keywords: ICL exchange; lens removal; implantable collamer lens; keratoconus; cornea